2020
DOI: 10.1002/acr.23847
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Use and Associations With Disease Activity, Health Status, and Mortality in Rheumatoid Arthritis

Abstract: Objective Better disease activity and quality of life have been observed among patients with rheumatoid arthritis (RA) who drink alcohol. This association might be explained by reverse causality. We undertook this study to identify predictors of change in alcohol use and to evaluate independent associations between alcohol use and RA activity and mortality. Methods Participants in Forward, The National Databank for Rheumatic Diseases, were asked about alcohol use (any versus none), and disease activity was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Similar to thyroid disease, diabetes and SLE, multiple epidemiological studies and several mechanistic studies support the protective role of light to moderate alcohol in RA in a J- or U-shaped dose-dependent manner 8 , 15 , 45–54 ( Table 1 ). In a meta-analysis study, both men and women had a reduction in RA risk over 10 years, with women experiencing the highest risk reduction.…”
Section: Protective Role Of Light-moderate Dose Of Alcohol In Autoimmune Diseasesmentioning
confidence: 89%
“…Similar to thyroid disease, diabetes and SLE, multiple epidemiological studies and several mechanistic studies support the protective role of light to moderate alcohol in RA in a J- or U-shaped dose-dependent manner 8 , 15 , 45–54 ( Table 1 ). In a meta-analysis study, both men and women had a reduction in RA risk over 10 years, with women experiencing the highest risk reduction.…”
Section: Protective Role Of Light-moderate Dose Of Alcohol In Autoimmune Diseasesmentioning
confidence: 89%
“…For E-DII, the item was shown to have decreased in 2017 compared to 2011 (ΔE-DII score negative). Since it has been reported that alcohol consumption may affect disease activity [ 27 ], we also investigated the effect of alcohol consumption instead of E-DII as an item. P values less than 0.05 (2-tailed) were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some early studies showed that fish [ 32 ], omega-3 fatty acids [ 33 ], and modest alcohol consumption [ 34 ] all decreased risk of RA. However, recent studies have dampened early enthusiasm that specific foods may potentiate or protect against RA, showing no association with fish [ 35 ], alcohol [ 36 ], coffee [ 37 ], meat [ 38 ], or dairy products [ 38 ]. A study within the Studies of Etiology of RA (SERA) cohort found one potential reason for discordant results.…”
Section: Dietmentioning
confidence: 99%